Measuring and predicting erosion and sediment yields on St. John, U.S. Virgin Islands - Ramos-Scharrón, Carlos E., author; MacDonald, Lee H., advisor; Wohl, Ellen, committee member; Dean, Denis J., committee member; Jackson, William, committee member (Colorado State University. Libraries, 2004)
Increased sediment delivery rates are believed to be causing adverse effects on the nearshore coral reef communities of St. John, U.S. Virgin Islands. The objectives of this study were to: (1) measure runoff and sediment yields from undisturbed hillslopes and a road segment; (2) measure and predict sediment production rates from natural sources and unpaved roads; and (3) develop and apply a GIS-based sediment yield model. Runoff on undisturbed hillslopes only occurred when storm precipitation exceeded 2-3 cm, while only 0.3 cm was needed to generate runoff from unpaved roads. Runoff coefficients for the undisturbed hillslopes averaged 3% and had a maximum of 8%, while the road segment had a mean runoff coefficient of 6% and a maximum of 70%. The road segment data were used to develop runoff models that combined the Green-Ampt infiltration with either an empirical unit hydrograph or a kinematic wave routing component. Both models underestimated runoff for storms with less than 1 cm of rainfall, but predictions improved when rainfall exceeded 1 cm. Streambanks produced sediment at a rate of 10 kg m-2 yr-1, and treethrow produced 0.17 tons per kilometer of stream per year. Annual sediment production rates from undisturbed hillslope plots ranged from 1-27 g m-2, while mean rates from undisturbed zero- and first-order catchments were 1 and 8 g m-2, respectively. Sediment production rates from unpaved road segments averaged 7.4 kg m-2 yr-1 and were significantly related to total precipitation and slope. After normalizing by precipitation and slope, the mean annual sediment production rate for roads graded within the last two years was 0.96 kg m-2 cm-1 m m-1, while rates for ungraded and abandoned roads were 0.56 and 0.071 kg m-2 cm-1 m m-1, respectively. Cutslopes were responsible for only 9% of road-segment scale sediment yields. STJ-EROS is a GIS-based system that uses empirical sediment production functions and delivery ratios to estimate watershed-scale sediment yields. STJ-EROS indicated that unpaved roads are increasing sediment yields by 5-40 times above undisturbed conditions. Predicted values were within the range of estimated sediment yields and bay sedimentation rates. The results indicate that road improvements are needed to protect the marine resources of St. John.
Keywords: hydrology; geology; geography; environmental science; hydrologic sciences; physical geography